Effects of Different Pre-drying Temperatures on Quality Characteristics and Flavor Components of Kernels from Dried Walnuts with Green Husks - GUO Congcong, CUI Yue, GAO Shuang, SU Boya, MA Aijin, QI Guohui, TIAN Yiling (Shipin Kexue)
This study investigated the impact of a new walnut processing technology on the quality and flavor of walnut oil in order to provide a theoretical basis for the development and application of this technology. Kernels from walnuts with green husks subjected to pre-drying treatment at 25, 120, 150 and 200 ℃ followed by natural drying and those treated directly by natural drying as a control were compared for their sensory quality, walnut oil quality, volatile organic compounds (VOCs). The results showed that pre-drying treatment resulted in higher overall sensory score of walnut kernels, the highest score of 34 being observed with pre-treatment at 150 ℃ for 60 min. Meanwhile, compared with the control, it increased the relative content of oleic acid in walnut oil and decreased the relative contents of linoleic and olenic acids. The relative content of unsaturated fatty acids in walnut oil was over 91%, the ratio of ω-6 to ω-3 polyunsaturated fatty acids (PUFAs) was within a reasonable range, and the basic physicochemical indicators met the national standards, indicating rich nutrition and good quality. Furthermore, pre-drying treatment increased the contents of most VOCs in walnut kernels. Walnut kernels pre-treated at 150 ℃ for 60 min contained the most abundant VOCs, and showed increased contents of aldehydes, ketones and heterocyclic compounds and decreased contents of alcohols, acids and esters compared with the control group. However, there was no significant difference in the content of terpenes between them. A partial least square-discriminant analysis (PLS-DA) model was generated based on the gas chromatography-ion mobility spectrometry (GC-IMS) results, which could well differentiate among walnut kernels with different pre-drying treatments, and 18 compounds were selected as the key VOCs affecting the flavor characteristics of walnut kernels with pre-drying treatments.